2011
DOI: 10.1037/a0025147
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of testing memory: Repeated retrieval can enhance eyewitness suggestibility.

Abstract: Eyewitnesses typically recount their experiences many times before trial. Such repeated retrieval can enhance memory retention of the witnessed event. However, recent studies (e.g., Chan, Thomas, & Bulevich, 2009) have found that initial retrieval can exacerbate eyewitness suggestibility to later misleading information-a finding termed retrieval-enhanced suggestibility (RES). Here we examined the influence of multiple retrieval attempts on eyewitness suggestibility to subsequent misinformation. In four experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 78 publications
1
57
1
Order By: Relevance
“…Contrary to the idea that RES is contingent on an initial cued recall test that draws attention to the later misinformation, the present results indicate that the RES effect might be more pervasive than previously thought. Overall, the effect has been found in free recall, cued recall, recognition Thomas et al, 2010), and source discrimination (Chan et al, 2012); it occurs at delays of 30 min, 48 hr, and a week between the witnessed event and final test (regardless of whether the misinformation occurs before or after the delay, Chan & Langley, 2011;Chan & LaPaglia, 2011), and it is found in both between-and within-subjects comparisons (Chan & LaPaglia, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the idea that RES is contingent on an initial cued recall test that draws attention to the later misinformation, the present results indicate that the RES effect might be more pervasive than previously thought. Overall, the effect has been found in free recall, cued recall, recognition Thomas et al, 2010), and source discrimination (Chan et al, 2012); it occurs at delays of 30 min, 48 hr, and a week between the witnessed event and final test (regardless of whether the misinformation occurs before or after the delay, Chan & Langley, 2011;Chan & LaPaglia, 2011), and it is found in both between-and within-subjects comparisons (Chan & LaPaglia, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the RES effect has been reported in various procedures (e.g., Chan & Langley, 2011;Chan & LaPaglia, 2011;, several important aspects of its generality remain unclear.…”
Section: Retrieval Enhances Eyewitness Suggestibility To Misinformatimentioning
confidence: 99%
“…More relevant to the present research is a counterintuitive finding that has been reported in a series of studies. Namely, that recalling the details of an event can increase eyewitness suggestibility to later presented misinformation (e.g., Chan, Thomas, & Bulevich, 2009;Chan & LaPaglia, 2011). This finding, termed retrieval-enhanced suggestibility (RES), is surprising because retrieval often enhances retention of an event (i.e., the testing effect; Roediger & Karpicke, 2006).…”
Section: Testing Increases Suggestibility For Narrative-based Misinfomentioning
confidence: 96%
“…That is, recent studies have demonstrated elevated false memory rates after taking a test (e.g., Chan & Langley, 2011; Chan & LaPaglia, 2011; Gordon & Thomas, 2014; Wilford, Chan, & Tuhn, 2014). This effect, labeled retrieval‐enhanced suggestibility (Chan et al, 2009), may be related to two underlying mechanisms: a focus on the misinformed items or the overwriting of the original memory trace because of testing.…”
mentioning
confidence: 99%
“…These include delay between the event and testing (Pansky, 2012) or the introduction of misinformation (Chan & LaPaglia, 2011), recall type (cued recall vs. free recall; Wang et al, 2014), form of misinformation (questions vs. narratives; LaPaglia & Chan, 2013), and contextual embedding of misinformation (LaPaglia, 2013). One factor that has rarely been examined is how information (i.e., the type of processing) is retrieved in the testing phase (but see Pansky & Tenenboim, 2011).…”
mentioning
confidence: 99%